Software-Defined Networking with OpenFlow - Second Edition. - Coker, Oswald (Packt Publishing, 2017)
Master OpenFlow concepts to improve and make your projects efficient with the help of Software-Defined Networking. About This Book Master the required platforms and tools to build network applications with OpenFlow Get to grips with the updated OpenFlow and build robust SDN-based solutions An end-to-end thorough overview of open-source switches, controllers, and tools Who This Book Is For If you are a network/system administrator or a system engineer and would like to implement OpenFlow concepts and take Software-Defined Networking on your projects to the next level, then this book is for you. If you are aware of broad networking concepts, and are familiar with the day-to-day operation of computer networks, you will find this book very beneficial. What You Will Learn Explore Software-Defined Networking and activities around SDN/OpenFlow including OpenFlow messages Hardware and software implementations of OpenFlow switches and experiment with Mininet GUI Learn about the role of OpenFlow in cloud computing by configuring and setting up the Neutron and Floodlight OpenFlow controller plugins Simulate and test utilities, and familiarize yourself with OpenFlow soft switches, controllers, virtualization, and orchestration tools Enhance and build environments for Net App development by installing VM's and tools such as Mininet and Wireshark Learn about hardware and software switches and get a feel for active open-source projects around SDN and OpenFlow In Detail OpenFlow paves the way for an open, centrally programmable structure, thereby accelerating the effectiveness of Software-Defined Networking. Software-Defined Networking with OpenFlow, Second Edition takes you through the product cycle and gives you an in-depth description of the components and options that are available at each stage. The aim of this book is to help you implement OpenFlow concepts and improve Software-Defined Networking on your projects. You will begin by learning about building blocks and OpenFlow messages such as controller-to-switch and symmetric and asynchronous messages. Next, this book will take you through OpenFlow controllers and their existing implementations followed by network application development. Key topics include the basic environment setup, the Neutron and Floodlight OpenFlow controller, XORPlus OF13SoftSwitch, enterprise and affordable switches such as the Zodiac FX and HP2920. By the end of this book, you will be able to implement OpenFlow concepts and imp ...